Kolaborasi Perguruan Tinggi Dan Pemerintah Desa Melalui Program Kuliah Kerja Nyata Dalam Mendukung Perencanaan Pembangunan Partisipatif - Olii, Tiara Primasari A.; Jalil L., Muhammad Fahril Abd.; Husain, Vania Dwi Maharani; Bukani, Tiara; Badjuka, Alexander H. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aims to analyze the collaboration between higher education institutions and village governments through the Community Service Program (Kuliah Kerja Nyata/KKN) in supporting participatory development planning. The research focuses on the implementation of the KKN program conducted by Universitas Negeri Gorontalo in the coastal area of Tomini Bay. The study employed a qualitative approach with a descriptive research design. The data were obtained from secondary sources, including KKN implementation reports, village development planning documents, regulations, scientific articles, and official publications from the government and universities. Data collection techniques were conducted through documentation studies and literature reviews, while data analysis used qualitative descriptive analysis through data reduction, data presentation, and conclusion drawing. The results indicate that the KKN program contributes to supporting participatory development planning through problem identification activities, village potential mapping, social observation, and community involvement in the implementation of development programs. The KKN program also demonstrates a collaborative governance pattern involving universities, village governments, and communities in supporting village development based on local needs. In addition to increasing community participation, the KKN program contributes to strengthening the capacity of village officials through administrative assistance, village data management, and facilitation of development deliberations. However, the implementation of the program still faces challenges, including limited implementation time, program sustainability, and the lack of optimal integration between KKN programs and village development planning documents. Therefore, strengthening the synergy between universities and village governments is necessary to ensure that the KKN program can support more participatory, responsive, and sustainable village development.